Real-time sketch rendering A system for non photo realistic rendering, mimicking graphite pencil drawings. - Örnvall, Gustav (My University, 2014)
This paper presents a real-time technique for rendering 3D surfaces in a pencil drawing style. It is fundamentally based on a paper which introduces a real-time pencil rendering system (Lee et al., 2006). The authors uses strokes drawn along the principal curvature directions to shade the interior of a 3D surface. The main focus of this thesis has been to implement a sketching system with a good support of arbitrary surfaces which are not uniformly tessellated and to provide results on par with the paper (Lee et al., 2006). To handle arbitrary surfaces which are not uniformly tessellated, a new way of computing a curvature direction eld has been implemented. This paper presents an implementation which visualize the outline of a surface and manages to sketch the geometry of complex surfaces in good quality.
Keywords: Data- och informationsvetenskap; Computer and Information Science